Determinantes da concessão de crédito livre para pessoas físicas no Brasil - Lopes, Ivan Campello (2017)
This paper aims to identify, with an econometric model, the main micro and macroeconomic variables that were responsible for the process of credit concession for individuals that took place in Brazil during 2004 and 2016, using quarterly data. The variables referred to bank spread, working population, confidence index, admission salary and country’s leverage, measured by credit as a percentage of product, were statistically significant. Finally, it was developed a prediction model based on VAR and the result shows that the model presented less uncertainty than a Randon Walk model, especially the prediction for the one quarter ahead.